Growth and survival rate vannamei shrimp (Litopenaeus vannamei) in various doses of fertilizer and density - Abdul Rakhfid; Udin Mauga (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2018)
Vannamei shrimp (Litopenaeus vannamei) is a commodity that is expected to not only increase options for farmers but also sustain the rise of shrimp farming business in Indonesia. One important factor in shrimp farming is the availability of feed. In addition to the availability of natural feed during cultivation, stocking density is also very influential in the survival rate and growth of shrimp vannamei. The research was conducted in September-December 2016 farms Bonea Village District of Lasalepa Muna with Test the different dosages with different stocking density. The study used a Random Group Factorial, which is based fertilization (Factor A) with three levels and stocking density (Factor B) as many as three levels, each with three replications so that all 27 units experimental unit. The results showed that the combination of factors dose of 0.7 g of urea + 0.9 g TSP and stocking density factor of 10 individuals per container provides prawn post larvae growth vannamei most excellent and a combination of factors Urea fertilizer dosage of 0.9 g TSP + 1.1 g and stocking density factor of 20 individuals per container provides a survival rate of post larvae vannamei most good. Water quality media for research in the range that is optimal for the growth and survival of post larvae vannamei.